TRANSFORMASI KARAKTER SISWA MELALUI KEGIATAN MARKET DAY SEBAGAI IMPLEMENTASI P5 DI SEKOLAH DASAR - Fitriyah, Afiyatul; Erfansyah, Nasrul Fuad; Munawir, Munawir; Sholichah, Siti Aminatu (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to describe the Market Day activity as an implementation of the Pancasila Student Profile Strengthening Project (P5) in fostering elementary students’ character. The research was conducted at SD Khazanah Ilmu, focusing on fifth-grade students who actively participated in the activity. The observed character aspects included responsibility, cooperation, confidence, and initiative throughout the planning, implementation, and evaluation stages. The study employed a qualitative approach with a case study design. Data were collected through direct observation and documentation, including sales reports, student worksheets, and teachers’ notes. Data were analyzed thematically to identify patterns of attitudes and behaviors reflecting character development. The findings indicated that the Market Day activity effectively fostered students’ character. Students demonstrated improved responsibility in fulfilling group roles, enhanced cooperation in completing tasks, increased confidence in communicating while offering products, and stronger initiative in decision-making when facing challenges. With consistent teacher guidance, students understood that the activity was not merely about buying and selling but also a meaningful learning experience. In conclusion, Market Day is a viable experiential learning strategy for character education in elementary schools.